Influence of Long-Term Anti-Seizure Medications on Redox Parameters in Human Blood - Danijel Jakovljević; Milan Nikolić; Vesna Jovanović; Teodora Vidonja Uzelac; Aleksandra Nikolić-Kokić; Emilija Novaković; Čedo Miljević; Maja Milovanović; Duško Blagojević (MDPI AG, 2024)
Background: Epilepsy is a chronic brain disease affecting millions of people worldwide, but little is known about the impact of anti-seizure medications on redox homeostasis. Methods: This study aimed to compare the effects of the long-term use of oral anti-seizure medications in monotherapy (lamotrigine, carbamazepine, and valproate) on antioxidant enzymes: superoxide dismutase, catalase, glutathione peroxidase, glutathione reductase, haemoglobin, and methaemoglobin content in erythrocytes, and concentrations of total proteins and thiols, nitrites, lipid peroxides and total glutathione in the plasma of epilepsy patients and drug-naïve patients. Results: The results showed that lamotrigine therapy led to lower superoxide dismutase activity (p < 0.005) and lower concentrations of total thiols (p < 0.01) and lipid peroxides (p < 0.01) compared to controls. On the other hand, therapy with carbamazepine increased nitrite levels (p < 0.01) but reduced superoxide dismutase activity (p < 0.005). In the valproate group, only a decrease in catalase activity was observed (p < 0.005). Canonical discriminant analysis showed that the composition of antioxidant enzymes in erythrocytes was different for both the lamotrigine and carbamazepine groups, while the controls were separated from all others. Conclusions: Monotherapy with anti-seizure medications discretely alters redox homeostasis, followed by distinct relationships between antioxidant components.